The PHANGS-JWST treasury survey: star formation, feedback, and dust physics at high angular resolution in nearby falaxieS - Lee, Janice C.; Schinnerer, Eva; Egorov, Oleg; Bigiel, Frank; Chevance, Mélanie; Glover, Simon; Kim, Jaeyeon; Klessen, Ralf S.; Kreckel, Kathryn; Neumayer, Nadine; Sormani, Mattia C.; Scheuermann, Fabian; et al. (The astrophysical journal. Part 2, Letters, 2023)
The PHANGS collaboration has been building a reference data set for the multiscale, multiphase study of star formation and the interstellar medium (ISM) in nearby galaxies. With the successful launch and commissioning of JWST, we can now obtain high-resolution infrared imaging to probe the youngest stellar populations and dust emission on the scales of star clusters and molecular clouds (∼5-50 pc). In Cycle 1, PHANGS is conducting an eight-band imaging survey from 2 to 21 μm of 19 nearby spiral galaxies. Optical integral field spectroscopy, CO(2-1) mapping, and UV-optical imaging for all 19 galaxies have been obtained through large programs with ALMA, VLT-MUSE, and Hubble. PHANGS-JWST enables a full inventory of star formation, accurate measurement of the mass and age of star clusters, identification of the youngest embedded stellar populations, and characterization of the physical state of small dust grains. ...
Gesehen am 06.12.2023